The impact of warmed and humidified CO2 insufflation during robotic radical prostatectomy: Results of a randomized controlled trial. Issue 3 (August 2019) - Oderda, Marco; Cerutti, Elisabetta; Gontero, Paolo; Manetta, Tilde; Mengozzi, Giulio; Meyer, Nicolas; Munegato, Stefania; Noll, Eric; Rampa, Paola; Piéchaud, Thierry; Diemunsch, Pierre
Background: Cool and dry gas insufflation during laparoscopy induces hypothermia and cytokine increase, with significant perioperative morbidity. Our aim was to assess if warmed and humidified CO2 insufflation with HumiGard™ device can achieve significant benefits over standard insufflation in terms of risk of hypothermia, cytokine response, blood gases, and intra- and postoperative parameters, in the setting of robot-assisted radical prostatectomy (RARP). Methods: This was a prospective, randomized controlled clinical trial. Sixty-four patients with prostate cancer undergoing RARP were randomized to receive warmed and humidified CO2 insufflation with HumiGard device, plus hot air warming blanket (treatment group, H + WB), or standard CO2 insufflation, plus hot air warming blanket (control group, WB). Body core temperature (BCT), plasma levels of IL-6 and TNF-α, pain scores, and intraoperative parameters were recorded. The data were analyzed according to the Bayesian paradigm. Results: Intraoperative BCT increased in both groups during surgery, with a statistically significant difference favoring group H + WB, ending at 0.2°C higher on average than group WB. No difference across groups was shown for cytokine levels. Blood gas parameters were not affected by warmed CO2 insufflation. No statistical differences were noted for pain scores and the other intra- and postoperative parameters. Conclusions: During RARP, warm and humidified CO2 insufflation with the HumiGard device was more effective than the standard CO2 insufflation in maintaining the patient's heat homeostasis, even if the difference was minimal. No imbalances were detected on blood gas analyses. No benefit could be shown in terms of cytokine levels and pain scores.